Establishment of vegetation in mine tailings using A. tumefaciens and organic matter - Sánchez, Deicy N. (2020)
ABSTRACT The landscape legacy of historical metal-mining activity can persist for decades. The most frequent strategies used for the remediation of contaminated soils include: the use of synthetic membranes to isolate contaminants, direct revegetation, or lime amendments. Looking for more cost-effective bioremediation approaches, we performed a set of greenhouse studies to determine what combinations of soil amendments would lead to the best vegetative response, and potentially associated reductions in soil arsenic (As) levels. In our first greenhouse experiment, we planted Leymus cinereus (basin wildrye) in tailings, compared (after 12 weeks) plant growth, and foliar metal concentrations across treatments. Amendments included single or factorial additions of lime, 5% organic matter (+OM), and an arsenic-oxidizing (+oxbact) strain of Agrobacterium tumefaciens (Agtu). For the first experiment, only one level of OM amendment was tested (5%) and a second greenhouse experiment with two levels of OM (1.5% and 5%). In this second experiment, Basin wildrye grown in soils amended with 5% OM generally did better than those grown in soils amended with 1.5% OM and even better in soils amendment with 5% OM + oxbact. These results suggest the combination of OM and Agtu oxbact strain could provide a potentially cost- effective approach to remediating As-contaminated soils.